Status studenta zatrudnionego na podstawie umowy zlecenia w świetle prawa ubezpieczeń społecznych. Perspektywa zleceniodawcy oraz zleceniobiorcy - Kazimierski, Damian; Wardecki, Władysław (Studia Prawa Publicznego, 2026)
A student employed on a mandate contract is excluded from the possibilityof joining the social insurance system. This issue is significant because, as highlighted in public discourse, replacing employment contracts with civil‑law contracts has become increasingly common. The article examines the legal framework applicable to student‑contractors in light of the economic and social costs and benefits, with particular emphasis on the consequences of uninsured risk. It considers not only the individual cost-benefit balance but also the potential burdens placed on society, since a student‑contractor is exposed to the same risks as an employee while being deprived of access to social insurance, a situation which may generate substantial social costs. The article identifies the ratio legis of the regulation, namely fostering young people’s competitiveness in the labour market and ensuring higher disposable income. It advances the thesis of a sui generis form of “internal social dumping” in the case of student‑contractors, a claim expected to provoke discussion within the doctrine. While the legislator’s aim is to strengthen students’ market competitiveness, this occurs at the expense of their protection against social risks. The comparison to internal dumping serves to highlight and illustrate the underlying objectives of the regulation. The purpose of the article is to analyse the effects of the current legal framework and to assess whether the ratio legis adopted thirty years ago remains adequate in today’s markedly different socio‑economic context. The discussion is supported by statistical data, and the article concludes with de lege lata and de lege ferenda recommendations.